2019
DOI: 10.1111/cdev.13327
|View full text |Cite
|
Sign up to set email alerts
|

Language Clearly Matters; Methods Matter Too

Abstract: Over two decades ago, the “30‐million‐word” gap rose to prominence after work by Hart & Risley (1995) suggested that children from families with low socioeconomic status (SES) heard fewer words than their peers from families with higher SES during their first 4 years of life. Recent research challenges the magnitude and even existence of this gap. However, due to methodological limitations, we know very little about the presence, magnitude, and settings in which there may be a word gap. Moreover, causal eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…Sperry et al (2019a) found evidence that contrasted with Hart and Risley’s (1995) original findings, demonstrating that caregiver talkativeness varied by community, rather than SES, and that the “word gap” essentially disappeared when a more inclusive definition of the language environment was employed (e.g., including speech from all caregivers and/or all ambient speech that a child overhears). Though the magnitude (or even existence) of a contextually driven word‐gap remains contentious (Golinkoff et al, 2019; Purpura, 2019; Sperry et al, 2019b), several studies do support this notion. For example, the speech of high‐SES mothers has been demonstrated to be more complex, more diverse, and contain more words as compared to the speech of mothers from low/middle‐SES backgrounds (Hoff, 2003; Huttenlocher, Vasilyeva, Waterfall, Vevea, & Hedges, 2007).…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
“…Sperry et al (2019a) found evidence that contrasted with Hart and Risley’s (1995) original findings, demonstrating that caregiver talkativeness varied by community, rather than SES, and that the “word gap” essentially disappeared when a more inclusive definition of the language environment was employed (e.g., including speech from all caregivers and/or all ambient speech that a child overhears). Though the magnitude (or even existence) of a contextually driven word‐gap remains contentious (Golinkoff et al, 2019; Purpura, 2019; Sperry et al, 2019b), several studies do support this notion. For example, the speech of high‐SES mothers has been demonstrated to be more complex, more diverse, and contain more words as compared to the speech of mothers from low/middle‐SES backgrounds (Hoff, 2003; Huttenlocher, Vasilyeva, Waterfall, Vevea, & Hedges, 2007).…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
“…We hypothesize that there are significant differences in children's early language environments between socioeconomic groups; however, we expect to find wide variability within groups (Schwab & Lew-Williams, 2016;Sperry et al, 2019) and a smaller between-group difference than Hart & Risley suggested (Gilkerson et al, 2017). We also expect to find effects of study methods on estimates of the word gap, as proposed by Purpura's (2019) commentary.…”
Section: Ses Differences In Infant Language Inputmentioning
confidence: 80%
“…Studies may find varying estimates of the "word gap" due to variable methods of collecting language samples (see Purpura, 2019 for a review). There are many approaches to quantifying language input; language samples are collected through researcher observations or audio-/video-recordings, either in a laboratory or in participants' homes, during a specified task SES DIFFERENCES IN INFANT LANGUAGE INPUT 7 or during everyday interactions, with researchers present or absent.…”
Section: Ses Differences In Infant Language Inputmentioning
confidence: 99%
“…This word gap translated into differences in the children's vocabulary and IQ (Hart & Risley, 1995). Hart and Risley's study has sparked rigorous debate (Golinkoff et al, 2019; Purpura, 2019; Sperry et al, 2019a), and its findings should be interpreted with caution. It has been criticized for its small sample size (Pan et al, 2005), the homogeneity of its low‐SES sample (Dudley‐Marling & Lucas, 2009; Sperry et al, 2019b), and for how talk was measured (Michaels, 2013; Sperry et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%